Freezability genetics in rabbit semen - Lavara, R.; Mocé, Eva; Baselga, M.; Vicente, José Salvador (2018)
The aim of this study was to estimate the heritability of semen freezability and to estimate the genetic correlation between frozen-thawed sperm traits and the growth rate in a paternal rabbit line. Estimated heritabilities showed that frozen-thawed semen traits are heritable (ranged between 0.08 and 0.15). In the case of Live-FT (percentage of viable sperm after freezing), the estimated heritability is the highest one, and suggests the possibility of effective selection. After the study of genetic correlations it seems that daily weight gain (DG) was negatively correlated with sperm freezability, but no further conclusions could be drawn due to the high HPD95%. More data should be included in order to obtain better accuracy for the estimates of these genetic correlations. If the results obtained at present study were confirmed, it would imply that selection for DG could alter sperm cell membranes or seminal plasma composition, both components related to sperm cryoresistance. (C) 2017 Elsevier Inc. All rights reserved.